Differentiation in higher education : a case study of Lesotho - Penduka, Mamthembu Mamachele (School of Education, 2016)
Differentiation has become a crucial policy driver in higher education systems that attempts to respond to global pressures for a highly skilled labour force, employ new technologies and adapt to unpredictable or volatile global product markets and rapid technological change. In order to be globally competitive, nations have to place knowledge production, accumulation, transfer and application at the centre of their national development strategies. This study investigates the case of Lesotho, a relatively small African country with a colonial past that has left a lasting imprint, both enabling and constraining, on many aspects of its education system. The aim of this explanatory case study was to identify differentiating trends within Lesotho's higher education system, focusing on two institutional types: the polytechnic and the university. These institutions were investigated at both institutional and programme level. The research question was "How differentiated is the polytechnic-university binary division in the public sector higher education system in Lesotho?" The sample for the study comprised two schools and two faculties at the polytechnic and the university respectively. One programme under each school or faculty was investigated.